Penggunaan Balaghatul Qur’an Sebagai Alternatif Pembelajaran Ilmu Balaghah - Ummah, Siti Rohmatul (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2021)
Al-Qur'an is a reference for studying Arabic literature. Unfortunately, most of the examples of lafaz that contain Arabic rules, including balaghah in language code books, are more often taken from Arabic poetry. Balaghah science itself is an advanced level of Arabic language rules after nahwu and shorof so that automatically the level of difficulty is also higher. To facilitate learning balaghah, there are several solutions, including taking a contrastive approach. This paper also aims to find alternative solutions to make learning balaghah easier for students. This article is a description of the results of classroom action research which is structured following the rules of qualitative applied research. The conclusions of this paper are 1) Balaghatul Qur'an here is defined as a discussion of lafaz-lafaz in the Qur'an that is fluent and contains the rules of balaghah science. 2) Learning balaghah science is the process of guiding students of balaghah science by the teacher so that students are able to understand, and apply the rules in balaghah science. 3) Balaghatul Qur'an can be applied as a component of learning balaghah science.